Protein interactions with osseointegrable titanium implants - Nascimento, Marvin do (2023)
This review aims to present the mechanisms of protein interactions with titanium dental implant surfaces. Methods: the analyses were based on searches of scientific articles available in English and Portuguese in PubMed (MEDLINE), Bireme (LILACS), Scielo, Web of Science and Google Scholar. Results: titanium dental implant treatments success rates (95-98%) are mainly due to the biocompatibility of titanium oxide on the implant surface, surgical techniques adopted, good implants manufacturing processes and biomechanical knowledge of the systems. Studies in past decades has empirically developed implant surfaces with significant changes in morphologies, roughness, wettability, surface energy, chemical composition, and chemical groups density or deposited molecules. These changes promoted better protein adsorption, osteoblast adhesion, and changes in the mechanisms involved in osseointegration. Thus, the time to put the implant in function has been reduced and the success rates have increased. In the osseointegration process, at the nanoscale, there is no contact between the bone and the implant surface, but there is the formation of a protein anchorage between the periosteum and the implant with an interface formed by proteins. In all the reactions between the body and the implant surface, the activities of fibronectin and integrin are essential, since they are responsible for transmitting information to the cell for its differentiation, adhesion and mobility. Conclusion: thus, the analyses of protein-implant interactions are indispensable for a better understanding of the performance of osseointegrated dental implants.